Identification and Analysis of Main Harmful Factors in Tailings pond. Issue 4 (September 2019) - Li, Quanming; Liu, Yinkun; Zhang, hong
Abstract: Combined with the particle size classification of the tailings pond, according to the corresponding laws and regulations of the safe production process, the tailings pond is identified and analyzed from four aspects: human, material, environment and management. From the source, the possible harmful factors in the tailings pond are pointed out, which will provide reference for the safe and effective operation of the tailings pond in the future.